Psychological Contract and Employee Work Motivation of PT. Ark of the Krian Brothers - Agus Dwi Cahyo (Psikologia : Jurnal Psikologi, 2015)
Work motivation can affects employee productivities that can be supported by the expectations that are desired the employee through the psychological contract. This study aims to investigate the relationship between psychological contract with employee motivation. This study used a quantitative correlational approach using the psychological contract as an independent variable (X) and work motivation as the dependent variable (Y). Sampling techniques used proportionate stratified random sampling of 80 employees of PT. Primary Wisesa Mandiri. The data analysis used a correlational technique of product moment pearson which is calculated with SPSS 16.0 for Windows, obtained the correlation coefficient (r) = 0.446; ρ = 0.001 <ρ = 0.01. Correlation value is positive, it means there was a significant relationship, ie, the higher the psychological contract owned by the higher employee motivation.